Skin Stem Cell Resource Potential for Peripheral Nerve Repair Due to trauma of post regional anasthesia - Christrijogo, Sumartono; Rantam, Fedik A; Rahardjo, Eddy; Tacharina, Martia R (KnE Life Sciences, 2017)
This study is undertaken to investigate the utilization of rabbit skin to be used as a source of stem cell, especially stem cells that is derived from the skin, to provide the healing and connection of damaged peripheral nerves. Based on the existing studies, there are many failures in the healing and connection of nerve due to trauma after regional anesthesia, and there is an opportunity that stem cells from the skin is potential to help the process of healing and even improvement in the failure of nerve grafting. 24 rabbits is used as experimental animals in this research. The 24 rabbit devided into 2 groups, the first group is a control group without suplementary therapy of rabbit skin stem cells, and the second group is the treated group that given rabbit skin stem cell as a supplementary therapy to treat the peripheral nerve damage post ansthesia. The result of this study shows that there is a significant differences between control and treated group. Statistical analysis was performed by using reliability test - intraclass correlation coefficient to assess interobserver variation and investigate the correlation. Keywords : Stem Cell, Skin, Peripheral Nerve, Nerve Repair.